Anti-inflammatory effects of a Chinese herbal tea, Shangqingyin, in mice and rats. Issue 2 (2017) - Tu, Long-Fang; Zhu, Si-Rui; Zhong, Yi-Fei; ,; He, Zi-Jian; Chen, Yong-Chang; Li, Xiao-Jun; Li, Yi-Fang; He, Rong-Rong
No abstract available